2022
DOI: 10.3390/ani12162090
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Animal Welfare and Farm Profitability in Cage and Free-Range Housing Systems for Laying Hens in China

Abstract: Several countries and regions have regulations in place to provide standards for the welfare of production animals, which have implications for breeding, management and trade. In the chicken egg production industry, the welfare impacts of this are not well understood. In the past decades, free-range systems were widely used for local chicken breeds in poultry industry in China, but their use has gradually declined due to the lower competitiveness compared to commercial cage systems. However, the practices of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In addition, the welfare of laying hens in China is a particular concern because some practices used for laying hens that have been phased out in other nations for animal welfare reasons remain common in China, such as non-enriched cage systems for egg production [84]. Therefore, laying hens may be a crucial species for future research.…”
Section: Research Frontiersmentioning
confidence: 99%
“…In addition, the welfare of laying hens in China is a particular concern because some practices used for laying hens that have been phased out in other nations for animal welfare reasons remain common in China, such as non-enriched cage systems for egg production [84]. Therefore, laying hens may be a crucial species for future research.…”
Section: Research Frontiersmentioning
confidence: 99%
“…It is worth noting that China is the largest producer and consumer of duck eggs in the world, with an output of ~4 million tons annually ( 16 , 17 ). A meta-analysis indicates that duck eggs contain higher levels of potentially toxic elements compared to chicken eggs ( 18 ). Due to the high Hg level in poultry eggs from Wuchuan compared to other areas, and the total Hg concentration in duck eggs exceeds that of chicken eggs ( 19 ), we hypothesize that concentrations of other heavy metals could be high in local poultry eggs (e.g., duck eggs).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of successful cage-free production exist in many regions of the world [ 22 ], and He et al [ 23 ] found with proper management, some free-range farms in China can be more profitable than caged farms. Beyond ensuring production, the successful marketing of egg products is crucial for supporting this production.…”
Section: Introductionmentioning
confidence: 99%